Aging of aluminum/iron-based drinking water treatment residuals in lake water and their association with phosphorus immobilization capability. (15th August 2015) - Wang, Changhui; Yuan, Nannan; Pei, Yuansheng; Jiang, He-Long
Abstract: Aluminum and Fe-based drinking water treatment residuals (DWTRs) have shown a high potential for use by geoengineers in internal P loading control in lakes. In this study, aging of Al/Fe-based DWTRs in lake water under different pH and redox conditions associated with their P immobilization capability was investigated based on a 180-day incubation test. The results showed that the DWTRs before and after incubation under different conditions have similar structures, but their specific surface area and pore volume, especially mesopores with radius at 2.1–5.0 nm drastically decreased. The oxalate extractable Al contents changed little although a small amount of Al transformed from oxidizable to residual forms. The oxalate extractable Fe contents also decreased by a small amount, but the transformation from oxidizable to residual forms were remarkable, approximately by 14.6%. However, the DWTRs before and after incubation had similar P immobilization capabilities in solutions and lake sediments. Even the maximum P adsorption capacity estimated by the Langmuir model increased after incubation. Therefore, it was not necessary to give special attention to the impact of Al and Fe aging on the effectiveness of DWTRs for geoengineering in lakes. Highlights: DWTRs before and after being incubated 180 days had similar structures. The SSA and pore volume after incubation drastically decreased. The Alox and Feox had minor changes, especially the Alox . Transformation of Al and Fe from oxidizable to residual forms was observed. DWTRs before and after incubation had similar P immobilization capabilities.